Viviparity and oviparity in termitophilous Rhiniidae (Diptera: Oestroidea) in the Western Ghats, India. (2nd April 2020) - Arce, Bernal J.; Clout, S.; Pat, Desirée L.; Bharti, Meenakshi; Pape, Thomas; Marshall, Stephen A.
ABSTRACT: Life history observations are documented for two species of rhiniid flies from the Western Ghats in India: larviposition and termitophagy in Stomorhina procula (Walker), and oviposition and saprophagy in Borbororhinia bivittata (Walker). Oviposition and larviposition strategies in termitophilous Rhiniidae (Diptera: Oestroidea) are discussed based on these examples.